Discovery of Aptamers Targeting the Receptor-Binding Domain of the SARS-CoV‑2 Spike Glycoprotein - Song, Yanling; Song, Jia; Wei, Xinyu; Huang, Mengjiao; Sun, Miao; Zhu, Lin; Lin, Bingqian; Shen, Haicong; Zhu, Zhi; Yang, Chaoyong (Analytical chemistry (Washington), 2020)
The World Health Organization has declared the outbreak of a novel coronavirus (SARS-CoV-2 or 2019-nCoV) as a global pandemic. However, the mechanisms behind the coronavirus infection are not yet fully understood, nor are there any targeted treatments or vaccines. In this study, we identified high-binding-affinity aptamers targeting SARS-CoV-2 RBD, using an ACE2 competition-based aptamer selection strategy and a machine learning screening algorithm. The K d values of the optimized CoV2-RBD-1C and CoV2-RBD-4C aptamers against RBD were 5.8 nM and 19.9 nM, respectively. Simulated interaction modeling, along with competitive experiments, suggests that two aptamers may have partially identical binding sites at ACE2 on SARS-CoV-2 RBD. These aptamers present an opportunity for generating new probes for recognition of SARS-CoV-2 and could provide assistance in the diagnosis and treatment of SARS-CoV-2 while providing a new tool for in-depth study of the mechanisms behind the coronavirus infection.